INTEGRASI ICT DALAM DINAMIKA INTERAKSI PENDIDIKAN: STUDI LITERATUR PADA HUBUNGAN GURU DAN SISWA - Jihan Tamamah (HIBRUL ULAMA, 2025)
The development of information and communication technology (ICT) has brought significant changes in the dynamics of educational interaction between teachers and students. The integration of ICT in the learning process not only enriches teaching methods but also increases student engagement and motivation. This literature study examines the role of ICT in shaping more interactive and collaborative communication in the educational environment, while identifying various challenges such as infrastructure limitations, teacher competencies, and ethical issues of technology use. The results show that optimal ICT utilization requires a targeted teacher competency development strategy and adequate policy support. Thus, ICT integration has the potential to improve the quality of education and create a more dynamic and inclusive learning environment in the digital era.